2013
DOI: 10.3390/molecules18043712
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Suzuki-Miyaura and Ullmann Type Homocoupling Reactions of 2- and 3-Halopyridines Using a Pd(OAc)2/Benzimidazolium Salt and Base Catalyst System

Abstract: A number of novel benzimidazole derivatives 1–4 were synthesized and the catalytic activity of these compounds in a catalytic system consisting of a benzimidazolium salt/Pd(OAc)2/K2CO3 were investigated in the Suzuki-Miyaura and Ullmann type homocoupling reactions under microwave irradiation. We obtained both cross coupling and homocoupling products of pyridine and some side products such as dimethylaminopyridine and unsubstituted pyridine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…'-dione type spiro compounds. 95,96 In connection with this, we also tried to explore catalytic effectiveness of the catalytic system including Pd salt and novel benzimidazole ligands in the cyclotrimerization reaction of phenyl isocyanate.…”
Section: Introductionmentioning
confidence: 99%
“…'-dione type spiro compounds. 95,96 In connection with this, we also tried to explore catalytic effectiveness of the catalytic system including Pd salt and novel benzimidazole ligands in the cyclotrimerization reaction of phenyl isocyanate.…”
Section: Introductionmentioning
confidence: 99%
“…Desired C Ar -C Ar bond formation was achieved efficiently with high regioselectivity. The 5-arylated compounds (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) were obtained in high conversions in the presence of KOAc as base, DMAc as solvent and complexes 2a-2h as catalysts.…”
Section: Discussionmentioning
confidence: 99%
“…Reagents and solvents 2-methylbenzyl chloride, 3methylbenzyl chloride, 2,4,6-trimethylbenzyl chloride, 2,3,5,6tetramethylbenzyl chloride, 2,3,4,5,6-pentamethylbenzyl chloride, 3,4,5-trimethoxybenzyl chloride, bis(benzonitrile)palladium chloride, N,N-dimethylformamidedimethylacetal, hexane, dimethylformamide, dichloromethane and diethyl ether were purchased from commercial suppliers (Merck, Aldrich, Alfa-Aesar and Fluka). CDCl 3 and DMSO-d 6 were used as solvents in all 1 H NMR and 13 C NMR analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22,23] In our previous studies, we used several in situ prepared palladium-N-heterocyclic carbenes derived from benzimidazole for the Suzuki, Heck and Buchwald-Hartwig reactions under microwave irradiation conditions and obtained promising catalytic results. [24][25][26][27][28][29][30] The use of a metal catalyst as nanoparticles generally accelerates the catalytic conversion and the use of nanoparticles in cross-coupling reactions has attracted a great deal of interest because of their effectiveness. Therefore, several studies have been reported relating to the use of palladium nanoparticles in cross-coupling reactions.…”
Section: Introductionmentioning
confidence: 99%